Galectin-9 and Tim-3 in gastric cancer: a checkpoint axis driving T cell exhaustion and Treg-mediated immunosuppression independently of anti-PD-1 blockade - Hill, Charlotte N.; Maita, Gabriela; Cabrolier, Camille; Aros, Constanza; Vega-Letter, Ana Maria; Gonzalez, Pamela; Kalergis, Alexis M.; Luz-Crawford, Patricia; Owen, Gareth I. (Frontiers in Immunology, 2025)
Immune checkpoint inhibitors have significantly advanced the treatment of gastric cancer (GC), yet therapeutic resistance remains common due to the immunosuppressive tumor microenvironment and redundancy among inhibitory checkpoints. Tim-3 (HAVCR2) is an emerging immune checkpoint receptor implicated in tumor immune evasion. However, the role of its ligand, Galectin-9 (Gal-9, LGALS9), in GC pathogenesis and therapy resistance remains poorly understood. We performed bioinformatic analysis of The Cancer Genome Atlas (TCGA) stomach adenocarcinoma (STAD) dataset to assess LGALS9 and HAVCR2 expression and their clinical correlations. We also evaluated associations between LGALS9 expression and immune cell signatures. Functional ex vivo assays were conducted to investigate the effects of Gal-9 on CD8⁺ T cell function and Treg suppressive activity in the context of Tim-3 signaling. Our analysis revealed that both LGALS9 and HAVCR2 are upregulated in gastric tumors and associated with poor patient survival. HAVCR2 expression was significantly higher in invasive adenocarcinomas. LGALS9 expression strongly correlated with signatures of CD8⁺ T cell dysfunction and increased infiltration of regulatory T cells (Tregs). Functionally, Gal-9 promoted Treg suppressive activity and CD8⁺ T cell dysfunction ex vivo through Tim-3 engagement, independently of PD-1 signaling. These findings suggest that Gal-9 contributes to immune evasion in GC by promoting Treg expansion and CD8⁺ T cell exhaustion, potentially driving resistance to anti-PD-1 therapy. We propose circulating Gal-9 as a candidate biomarker of anti-PD-1 resistance and support the rationale for combined blockade of PD-1 and Tim-3 to enhance immunotherapeutic efficacy in GC.